Analysis of The Students Number Sense on Integer Operations Reviewed From Cognitive Style - Baiq Filaily Komariani; Lalu Sucipto; Kiki Riska Ayu Kurniawati (Universitas Muhammadiyah Mataram, 2020)
This research aims to describe the number of sense capabilities of students MTs. Islam Selaparang Putra on integer operations are reviewed from cognitive style. This research is qualitative descriptive research. The subject of this study was 4 people, 2 field-dependent subjects and 2 field-independent subjects. The instruments used are group embedded figures test, number sense test sheets, and interview guidelines. Data analysis techniques are done by reducing data, presenting data, and drawing conclusions. The validity of the data is using the triangulation method. The number sense capability is analyzed based on the number sense indicator which is (1) understand the value and symbol numbers, (2) understand the relationship between numbers, (3) understand the decimal number system, (4) understand the meaning of number operations, (5) understand the relationship between number operations, (6) Perform calculations correctly, (7) have a wide range of settlement strategies, (8) have the ability to estimate the value of a calculation. The result of this research is the subject of field-dependent less using the number of his sense in answering questions and only meet one indicator. While the subject of field-independent uses the number of his sense to answer the problem and fulfill two indicators.